Kajian Kesantunan dalam E-Mail Permohonan yang Ditulis oleh Penutur Jepang dan Pembelajar Indonesia - Wahyuningtias, Hani (Lingua Cultura, 2014)
Nowadays electronic mail (e-mail) is a communication tool that is often used in everyday life. One of the utilizations of e-mail is used in practical purposes such as making a request. This paper provided views on linguistic politeness in submitting an e-mail containing the request based on e-mail data written by native speakers of Japanese (J) and the Indonesian Japanese language learners (IJL). The data was analyzed using the theory of politeness expressed by Brown and Levinson. This paper focused on the strategy that what more likely was to be used by J and IJL in the expression of request. In the final part, it concluded the view about what should be considered in connection with the linguistic politeness in Japanese e-mail containing request. It was intended for learners of foreign language, especially Indonesian people, to know the limitation of politeness, so that IJL will not repeat the same mistakes in the future.